Exploring Strategies to Enhance Psychology Students’ Learning Motivation in Statistics Course: A Qualitative Study at Airlangga University - Dame Triulina Hutasoit; Nono Hery Yoenanto (Universitas Mercu Buana Yogyakarta, 2025)
This study explored strategies to enhance learning motivation among psychology students in the Statistics course at Airlangga University. Many students initially perceived statistics as a difficult and irrelevant subject, often causing anxiety and disengagement. Using a qualitative case study approach, data were gathered from five students through semi-structured interviews and were analyzed thematically. The findings revealed five central themes: students’ negative initial perceptions of statistics, the importance of connecting statistical concepts to real-world psychological practice, the role of peer and lecturer support in maintaining emotional engagement, the effectiveness of interactive and visual learning methods, and the use of personal strategies such as self-reflection and goal setting. These results underscore the importance of fostering autonomy, competence, and social relatedness in academic settings, suggesting that motivational challenges in complex courses such as Statistics can be addressed through humanistic and contextually relevant learning strategies.